Implementasi kurikulum merdeka dalam pembelajaran bahasa Arab - Wahidah, Shofiyah Risalatul (Maliki Interdisciplinary Journal, 2024)
Education is a primary focus in various countries to prepare future generations to face global challenges. A state-regulated curriculum plays a crucial role in achieving educational goals, with the quality of the curriculum being a benchmark for educational success. In Indonesia, the implementation of the Kurikulum Merdeka emerged as a response to the learning crisis and setbacks caused by the Covid-19 pandemic. This curriculum emphasizes freedom, innovation, and students’ adaptability, in line with Ki Hajar Dewantara’s concept that highlights the freedom to learn and the development of creativity. The Kurikulum Merdeka is student-centered learning, designing learning activities to encourage student activity and creativity. In Arabic language learning, the Kurikulum Merdeka is implemented according to KMA Number 183 of 2019, with an approach that enhances the quality of learning and strengthens students’ competencies while integrating cultural, historical, and value contexts of the Arabic language.